Traces of Reciprocal Exchange: From Roman Pictorial Models to the World’s Earliest Depictions of Some Narrative Motifs in Andhra Reliefs - Zin, Monika (Religions, 2020)
Based on a selection of examples from the sculptural art of Andhra, the paper discusses what possibly motivated the inclusion of motifs and stylistic elements from the ancient Mediterranean into the Buddhist art of the region. While in some cases such adaptations may have been driven by the need to find suitable solutions for the depiction of critical events or by the fact that a foreign motif tied in perfectly with already existing concepts, and thus, reinforced the message to be conveyed, in other cases no such reasons can be detected. Artists seem to have used foreign image types and stylistic variations deliberately to show their supreme craftsmanship or to add aesthetic sophistication to the image programme. The artists of Andhra, therefore, can by no means be regarded as epigones slavishly adhering to the examples set by the Mediterranean; the region—which is the place where narratives later spreading over large parts of Asia and Europe were first depicted—rather has to be regarded as on par with the classical cultures of Greece and Rome in terms of artistic versatility and creativity.